Influence of Na and K contents on the antibacterial response of piezoelectric biocompatible NaxK1-xNbO3 (x = 0.2–0.8). (June 2021) - Khare, Deepak; Singh, Angaraj; Dubey, Ashutosh Kumar
Highlights: Synergistic effect of variation in Na and K contents and polarization to improve the antibacterial response of Nax K1-x NbO3 (x = 0.2 - 0.8). Polarized surfaces of sodium (Na0.8 K0.2 NbO3 ) and potassium (Na0.2 K0.8 NbO3 ) rich NKN exhibit maximum reduction in bacterial viability. Generation of reactive oxygen species (ROS) is higher on the positively polarized surfaces of sodium and potassium rich NKN ceramics. Abstract: Owing to the potential risk of bacterial infection during- or post-surgical operations, the development of antibacterial prosthetic orthopedic implants is in continuous thrust. In this perspective, the present work investigates the synergistic effect of surface polarization and compositional variation of Na and K contents in biocompatible Nax K1-x NbO3 (x = 0.2 to 0.8) in improving their antibacterial performance. The processing parameters were optimized to obtain dense and phase pure piezoelectric Nax K1-x NbO3 (x = 0.2−0.8). The sintered samples were polarized at the temperature and voltage of 500 °C and 20 kV, respectively, for 30 min. The effect of surface polarization on viability and adhesion of S. aureus and E. coli bacteria on piezoelectric Nax K1-x NbO3 (x = 0.2−0.8) as well as hydroxyapatite or HA (control) samples have been analyzed, quantitatively as well as qualitatively. The viability of S. aureus bacteria was reduced by (41, 29, 50 %) and (28, 20, 30 %) on the positively and negatively polarized surfaces of Nax K1-x NbO3 (x = 0.2, 0.5, 0.8) samples, respectively, as compared to non-polarized HA. For E. coli bacteria, the negatively and positively polarized surfaces of Nax K1-x NbO3 (x = 0.2, 0.5, 0.8) samples show reduced viability of bacteria by (49, 37, 52 %) and (31, 24, 45 %), respectively, as compared to non-polarized HA. In addition to surface charge polarization, sodium (x = 0.8) and potassium (x = 0.2) rich compositions further improve the antibacterial performance of Nax K1-x NbO3 . Various assays associated with enzymatic activities were also performed to examine the effect of polarization and compositional variation on the reactive oxygen species (ROS) generation. The ROS generation and ROS induced bacterial damage was observed to be maximum on the positively polarized surfaces of sodium (x = 0.8) and potassium (x = 0.2) rich compositions of Nax K1-x NbO3 . These enzymatic activities results were further corroborated with qualitative antibacterial analyses (live/ dead assay). Although, non-polarized Nax K1-x NbO3 (x = 0.2, 0.5, 0.8) samples illustrated significantly higher antibacterial response as compared to HA, quantitative and qualitative results reveal that polarized surfaces of sodium (Na0.8 K0.2 NbO3 ) and potassium (Na0.2 K0.8 NbO3 ) rich Nax K1-x NbO3 samples show the maximum reduction in viability and adhesion of S. aureus and E. coli bacteria.